A Contextual Semi-Assisted Project-Based Learning on Ocean Wave Energy: Pre-service Physics Teachers’ Perceptions - Muhammad Satriawan; Liliasari Liliasari; Wawan Setiawan; Ade Gafar Abdullah; Rosmiati Rosmiati (Universitas Muhammadiyah Makassar, 2021)
The lack of technological innovation in the utilization of ocean wave energy as a renewable energy source is caused by a lack of public knowledge about this matter. Therefore, it needs to be introduced early, especially to pre-service teachers through innovative and fun learning. The aim of this study was to identify the responses of pre-service physics teachers about the learning program to introduce the concept of utilizing ocean wave energy. The research subjects were 31 sixth semester students who are taking environmental physics lectures in the physics education study program at one of the teachers' university in West Nusa Tenggara Province for the 2019/2020 academic year. The sample was taken by using purposive sampling technique. Data collection was carried out by means of observation, interview, and questionnaire techniques. All data collected were then analyzed simultaneously descriptively. The findings of this study showed that almost 90% pre-service physics teacher students agreed that the learning program had a positive impact on increasing interest, motivation, critical thinking skills, and creative thinking skills, and made them easier to solve problems and grow solid cooperation. Therefore, it can be concluded that pre-service physics teacher students agree to the use of semi-assisted project-based learning programs with contextual problems.